Systemic error: measuring gender in criminological research - Valcore, Jace L. (Criminal justice studies, 2018)
This study examines how sex and gender are measured and operationalized in studies on criminology and criminal justice (CCJ) through content analysis of peer-reviewed journals. Despite that they are distinct and not always parallel, the terms sex and gender are often used interchangeably in CCJ research. Moreover, despite increasing recognition that gender-responsive practices are important at every stage of the criminal justice process, gender is almost exclusively measured as a male-female binary, miscategorizing and failing to properly account for those who do not fit in one of those gender identities. There are important implications for the safety of such individuals, as both victims and offenders throughout the criminal justice process, therefore it is essential that we more accurately measure gender in this field. Recommendations for improvement are addressed.